1998
DOI: 10.1677/joe.0.1560373
|View full text |Cite
|
Sign up to set email alerts
|

Levels of messenger RNA encoding ovarian receptors for FSH and LH in cattle during superovulation with equine chorionic gonadotrophin versus FSH

Abstract: This study tested the hypothesis that luteal LH receptor (LHr) and follicular LHr and FSH receptor (FSHr) steadystate mRNA levels are greater during superovulation with equine chorionic gonadotrophin (eCG) compared with that with FSH. Heifers were stimulated with eCG (n=10) or FSH (n=10), and ovaries were recovered the day before and at 12 and 24 h after luteolysis was induced with prostaglandin F 2 (PGF 2 ). Total RNA was purified from individual follicles and corpora lutea. Steady-state levels of LHr and FSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
5
1
3
Order By: Relevance
“…Treatment with eCG increased fertility in Bos indicus cows submitted to TAI, promoting improvement in the final follicular development, which raises the ovulation rate in Bos indicus cows ( Sá Filho et al, 2010a andSales et al, 2011). In addition, there is evidence that eCG increases estradiol production during proestrous ( Soumano et al, 1998) and increases P4 in the subsequent estrous cycle ( Sá Filho et al, 2010c).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with eCG increased fertility in Bos indicus cows submitted to TAI, promoting improvement in the final follicular development, which raises the ovulation rate in Bos indicus cows ( Sá Filho et al, 2010a andSales et al, 2011). In addition, there is evidence that eCG increases estradiol production during proestrous ( Soumano et al, 1998) and increases P4 in the subsequent estrous cycle ( Sá Filho et al, 2010c).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that gonadotropin regulation of bovine FSHR and LHCGR protein content during follicular growth, ovulation, and luteinization is associated with analogous changes in their respective receptor mRNA levels (Soumano et al 1998). Gonadotropin receptors are structurally related members of the seven transmembrane domain G protein-associated receptor superfamily (Vassart et al 2004).…”
Section: Expression Of Gonadotropin Receptorsmentioning
confidence: 99%
“…The distribution pattern and expression levels of gonadotropin receptors in healthy ovaries have been evaluated by several methods, including conventional and real-time RT-PCR, northern blot assays, and in situ hybridization (Ireland & Roche 1983, Xu et al 1995, Bodensteiner et al 1996, Rajapaksha et al 1996, Bao et al 1997, Evans & Fortune 1997, Bao & Garverick 1998, Soumano et al 1998, Odore et al 1999, Calder et al 2001, Manikkam et al 2001, Robert et al 2003, Braw-Tal & Roth 2005, Luo & Wiltbank 2006, Mihm et al 2006, Nogueira et al 2007, Nimz et al 2009). In recent studies conducted in our laboratory, we analyzed the relative expression levels of LHCGR and FSHR in follicular cysts of cows with COD and antral follicles of healthy animals by real-time RT-PCR and, in agreement with that found by other authors, we found that mRNA expression of FSHR in antral follicles was exclusively localized to granulosa cells and it decreased as follicle size increased, and that LHCGR mRNA was detected in theca cells of antral follicles of all sizes and in the granulosa cells of large antral follicles, being theca cells of medium antral follicles, the ones that showed the highest expression (Marelli et al 2014).…”
Section: Expression Of Gonadotropin Receptorsmentioning
confidence: 99%
“…Estradiol is synthetized in granulosa cells through cytochrome P450 aromatase complex and by the enzyme 17β-hydroxysteroid dehydrogenase. Furthermore, some studies reported that eCG increases E2 production by increasing the amount of mRNA for cytochrome P45017α [40,41], and FSH and LH could trigger this enzyme complex stimulating E2 production and follicle development [42][43][44]. These different results between our study and the literature is probably due to the different techniques, because E2 was measured in follicular fluid or media cultured with granulosa cells.…”
Section: Discussioncontrasting
confidence: 80%